EFFECT OF CHITIN AND CHITOSAN DERIVED FROM CRAB SHELL AND SHRIMP HEAD ON THE UNFROZEN WATER AND DENATURATION OF LIZARD FISH MYOFIBRILS DURING FROZEN STORAGE - Y S Dharmanto (JOURNAL OF COASTAL DEVELOPMENT, 2003)
The shrimp head and crab shell are rich in chitin and chitosan that can be used as the raw material in various industries. Chitin is composed of 2-acetamido-2-deoxy-D-glucose, whereas chitosan is composed primarily of glucosamine, 2-amino-2-deoxy-D-glucose. Chitin and chitosan can commercially be manufactured in the forms of powder, flake, chitinazed, nitrate chitin and 77-red chitin. Chitin and chitosan is of benefit to neutralize toxicity of polluted water, a pivotal role for strengthening the emulsion system, binding water and fat, advancing the loaf volume of bread, and for binding food drying, purification of apple, beer, wine extracts, etc. To find out the effect of chitin and chitosan of shrimp head and crab shell on the unfrozen water and denaturation of lizard fish myofibrils during frozen storage, chitin and chitosan were added at certain ratios 0; 2.5 – 7.5 g / 100 g, with non chitin and chitosan treatments as control. Changes of unfrozen water in myofibrils during frozen storage were studied based on the relationship between water content and transition heat, which was determined by Differential Scanning Calorimeter (DSC), whereas Ca-ATPase activity was analyzed using formula introduced by Katoh et. al., (1977). During frozen storage, chitin and chitosan treatments influenced the amount of unfrozen water and Ca-ATPase activity. Without chitin and chitosan the amount of unfrozen water in myofibrils decreased rapidly, whereas the decrease was moderate when myofibrils received chitin and chitosan. The change in Ca-ATPase activity exhibited a similar tendency to those of the unfrozen water indicating a close correlation between Ca-ATPase activity and amount of unfrozen water.